1995
DOI: 10.1002/ana.410380423
|View full text |Cite
|
Sign up to set email alerts
|

Reversible dementia and apparent brain atrophy during valproate therapy

Abstract: Two children developed severe cognitive and behavioral deterioration suggestive of a degenerative disease while being treated with sodium valproate for idiopathic, localization-related epilepsy with centrotemporal spikes. Magnetic resonance imaging revealed marked central and generalized cortical and cerebellar atrophy. In both patients, clinical symptoms and signs cleared in a few weeks following valproate withdrawal. The magnetic resonance imaging appearance improved within 3 months in 1 of the patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 11 publications
3
61
0
2
Order By: Relevance
“…For example, gray matter volume (cortical and subcortical) has been reported to be negatively correlated with disease duration in GGE,7, 10, 14, 24 although some studies did not find thalamic volume and disease duration to be correlated,3, 23 which may relate to the patient group selected, or to other factors such as seizure frequency or AED treatment. The effect of AED treatment is unclear: although reports of animal studies have indicated effects on brain development, there are only case reports available in humans that confirm these effects 13, 31, 32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, gray matter volume (cortical and subcortical) has been reported to be negatively correlated with disease duration in GGE,7, 10, 14, 24 although some studies did not find thalamic volume and disease duration to be correlated,3, 23 which may relate to the patient group selected, or to other factors such as seizure frequency or AED treatment. The effect of AED treatment is unclear: although reports of animal studies have indicated effects on brain development, there are only case reports available in humans that confirm these effects 13, 31, 32…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of brain morphology in GGE have been carried out in populations of patients with a longstanding diagnosis and on long‐term antiepileptic drug (AED) treatment; both factors could affect brain morphology 12, 13. This precludes unequivocal attribution of abnormalities in brain morphology to the underlying etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of drugs on the neocortex are largely unknown. While some studies suggest that phenytoin 31 induces cerebellar atrophy and valproic acid 32 pseudoatrophy of the brain, others have shown that these drugs may have neuroprotective effects and promote neurogenesis. 33,34 A recent randomized controlled trial 35 demonstrated that 58% of surgically treated patients were seizure free at 1 year, compared with 8% of medically treated patients.…”
Section: Cross-sectional Analysis Effects Of Durationmentioning
confidence: 99%
“…A decrease in full-scale IQ has also been noted. 37 These reports indicate that dementia may develop shortly after the introduction of the valproate, 36,37 or the dementia may have an insidious and progressive course that becomes obvious only after chronic treatment. 38 Both the encephalopathy observed on MRI scans and the cognitive changes remit within days of discontinuation of the medication.…”
Section: Valproatementioning
confidence: 99%